Bis-imidazole ring-containing bipolar organic small molecule cathodes for high-voltage and ultrastable lithium-ion batteries. Issue 1 (7th December 2022) - Zheng, Liping; Ren, Jiayi; Ma, Huige; Yang, Mingsheng; Yan, Xiaorong; Li, Rui; Zhao, Qian; Zhang, Jianze; Fu, Haifeng; Pu, Xiong; Hu, Mingjun; Yang, Jun
Abstract : A bis-imidazole ring-containing bipolar conjugated organic small molecule was used as the cathode of lithium ion batteries for the first time and showed high average discharge voltage, salient specific capacity and great cycling stability. Abstract : Organic cathode materials are attractive for rechargeable lithium-ion batteries due to their advantages in sustainability and designability of the molecular structure as well as the high upper limit of theoretical capacity. However, their practical application faces the problems of a short cycle life and low working potential. To address these issues, we synthesized a novel bis-imidazole ring-containing organic small molecule compound 2, 6-bis(4-(diphenylamino)phenyl)benzo[1, 2-d:4, 5-d′]diimidazole-4, 8(1 H, 5 H )-dione (BNBQ). It possesses bipolar charge storage characteristics with n-type CO, p-type triphenylamine groups and p-type bis-imidazole rings, endowing it with a good specific capacity and high redox potential. Attributed to the large conjugated molecular structure, strong π–π interaction and good crystallinity, it exhibits excellent electrochemical performances. As a consequence, Li-ion half-cells assembled based on the organic cathode and lithium anode deliver high average discharge voltages of about 3.64 V, salient initial specific capacity (133 mA h g −1 at 100 mA g −1 ), and good capacity retention (63% after 5000 cycles at 1000 mA g −1 ), outperforming most previously reported bipolar organic small molecular cathodes of lithium-ion batteries. This is the first report that the active bis-imidazole rings were employed for energy storage, and will further enrich the library of organic electrochemical active groups.